Investigation of the Friction Factor-Reynolds Number Relationship for Flow through Packed Beds - nan, nan (Iraqi Journal of Civil Engineering, 2010)
AbstractThis work presents the study of water flow through a packed bed containing spherical glass particles distributed randomly. The packed bed was 7.62 cm in diameter and 57 cm long. The glass particles were 0.42, 0.50, 0.61, 0.79 and 1.01 cm in diameter. Different flow rates of fluid were used which expressed by modified Reynolds number. The experiments were carried out at laboratory temperatures at city water temperature (25◦C) for water flow. Many variables were studied in this work such as fluid type, flow rate and the packing porosity, in order to study the effect of these variables on the pressure drop and friction factor. The results showed that the pressure drop through a packed bed is highly sensitive to the packing porosity which has a significant effect on the friction factor. It was found that as the bed porosity increases the friction factor values as well as the pressure drop values decrease.Empirical correlation for friction factor as a function of Reynolds number for water flow through packed of mono size packing has been made, and can be written as follows: The correlation coefficient was 0.97406 and percentage of average errors was 2.44%.